Zinc is an Antioxidant and Anti-Inflammatory Agent: Its Role in Human Health - Prasad, Ananda S. (Frontiers in Nutrition, 2014)
Zinc supplementation trials in the elderly showed that the incidence of infections was decreased by approximately 66% in the zinc group. Zinc supplementation also decreased oxidative stress biomarkers and decreased inflammatory cytokines in the elderly. In our studies in the experimental model of zinc deficiency in humans, we showed that zinc deficiency per se increased the generation of IL-1β and its mRNA in human mononuclear cells following LPS stimulation. Zinc supplementation upregulated A20, a zinc transcription factor, which inhibited the activation of NF-κB, resulting in decreased generation of inflammatory cytokines. Oxidative stress and chronic inflammation are important contributing factors for several chronic diseases attributed to aging, such as atherosclerosis and related cardiac disorders, cancer, neurodegeneration, immunologic disorders and the aging process itself. Zinc is very effective in decreasing reactive oxygen species (ROS). In this review, the mechanism of zinc actions on oxidative stress and generation of inflammatory cytokines and its impact on health in humans will be presented.